Renewable Energy Business Waste Management at Bantargebang TPST as an Alternative Fuel for Cement Industry - Hartono, Rakhmad Sugih; Mujanah, Siti; Fianto, Achmad Yanu Alif (Jurnal Locus Penelitian dan Pengabdian, 2025)
The hospitality industry in Indonesia, as a crucial component of the tourism sector, faces significant challenges in efficiently managing food supplies. This study aims to design an application that connects hotels with food suppliers, addressing the key issues of supply and resource management. The research methodology employed is qualitative descriptive, which includes literature review and interviews with various stakeholders in the hospitality industry. Findings indicate that the COOK LINK application has great potential to enhance hotel operational efficiency with standout features such as online payments, real-time stock tracking, and more effective customer complaint management. The analysis further demonstrates that by integrating technology into the management of food supplies, hotels can reduce the risk of shortages and ensure optimal quality of raw materials. The implications of this research are vital for developing differentiation strategies within the hospitality industry and creating opportunities to leverage technology to meet market competition. With the implementation of this application, it is anticipated that customer satisfaction will improve and lead to sustainable growth within the hospitality sector, ultimately supporting the advancement of the tourism industry in Indonesia.